Biochemical and microbiological changes of pink perch (Nemipterus japonicus) surimi stored at different temperatures - Singh, R K; Balange, A K (Indian Journal of Fisheries, 2011)
Investigations on factors responsible for spoilage of frozen surimi of pink perch (Nemipterus japonicus) stored at ambient (25 to 280 C), refrigerator (6.5 to 7.50 C) and at deep freezer temperatures (-8 to -100 C), in terms of organoleptic quality, bacterial load and biochemical indices indicated that at ambient temperature, frozen surimi can be preserved for about 8 hrs, while at refrigerator temperature up to 5 days and at deep freezer temperature up to 60 days. Bacterial count, trimethylamine and total volatile nitrogen values increased with storage time while, organoleptic score decreased. Nutrient contents and gel strength of surimi decreased while, moisture and whiteness increased with storage period.